Herb Medicines against Osteoporosis: Active Compounds & Relevant Biological Mechanisms - Wu, Lei; Ling, Zhuoyan; Feng, Xueqin; Mao, Caiping; Xu, Zhice (Current Topics in Medicinal Chemistry, 2017)
Osteoporosis is one of common bone disorders, affecting millions of people worldwide. Treatments of osteoporosis consist of pharmacotherapy and non-pharmacological interventions, such as mineral supplementation, lifestyle changes, and exercise programs. Due to the minimum side effects and favorable cost-effective therapeutic effects, herbal medicine has been widely applied in clinical practices for more than 2,000 years in China. Of the many traditional formulas reported for treating bone diseases, 4 single herbs namely (1) Herba Epimedii, (2) Rhizoma Drynariae, (3) Fructus Psoraleae, and (4) Cortex Eucommiae, are considered as the featured
Keywords: treatment